BIOMORPHOLOGICAL CHARACTERISTICS OF "RABBIT OTODECTOSIS", ITS PLACE IN SYSTEMATICS, LABORATORY DIAGNOSIS (Intent Research Scientific Journal, 2023)
Rabbit otodectosis is characterized by the appearance of various inflammatory foci due to parasitism of very small, microscopic itchy mites belonging to the suborder Acariformes in the auditory organs, in particular, in the auricle, auditory canal, and tympanic membrane, and the rabbit breeding network It is one of the factors hindering the development. In the article, the clinical signs of the disease in rabbits, course, bio-ecology, morphology, laboratory diagnosis, and zoological systematics of the causative agent are covered.